Abdomen Radiography With Suspension Of Corpus Alienu (Implicated By An Arrow) at Adam Malik General Hospital Medan 2024 - Aritonang, Fitler; Sinaga, Sahat; Sihombing, Ismadi; Barus, Syafril; Kem, Sarma Dewi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
Injuries caused by stuck arrows are rare but potentially life-threatening, especially when they hit vital organs. This study aims to evaluate the abdominal radiographic examination procedure in cases of corpus alienum, where there is a foreign object (arrow) stuck in the patient. The study was conducted at the Radiology Installation of H. Adam Malik Hospital Medan, using conventional X-ray modalities and image processing with Computed Radiography (CR). The study emphasized the importance of using appropriate projections, such as Antero-Posterior (AP) erect, Antero-Posterior (AP) supine, and lateral projections to ensure accurate diagnosis. The results show that these projections provide optimal images in determining the location and condition of the corpus alienum, which is crucial for further medical treatment. This study makes a practical contribution as a reference in performing abdominal radiography procedures in similar cases and enriches the literature related to radiographic examination in corpus alienum cases.